2009
DOI: 10.1590/s0104-42302009000400010
|View full text |Cite
|
Sign up to set email alerts
|

Neonatally-induced diabetes: lipid profile outcomes and oxidative stress status in adult rats

Abstract: 0.05) in the n5-STZ animals when compared to control group. However n5-STZ animals showed a significant decreased HDL-cholesterol rate (p<0.05). CONCLUSION: This streptozotocin-induced diabetes model in rats caused hyperglycemia (120-360mg/dL), characterizing mild diabetes. This glycemic level led to HDL-lipoprotein alteration, which was not sufficient to impair antioxidant enzyme activities or determination of lipid peroxidation in adult life of rats. Further this experimental investigation contributed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
3
14
1
2
Order By: Relevance
“…En otros estudios en el mismo modelo animal llevados a cabo por nuestro equipo de investigación, se ha corroborado esta conclusión, pues en el grupo inoculado por vía subcutánea se encontraron alteraciones en los parámetros oxidativos y metabólicos (principalmente en el perfil renal) (27). Sin embargo, en la literatura científica se ha registrado la presencia de diabetes moderada con la inoculación intraperitoneal de estreptozotocina en animales durante el periodo neonatal, aunque con variaciones en las dosis, los momentos y las cepas utilizadas (9,13,28,29), lo cual corrobora que el modelo debe seleccionarse en función del propósito y las condiciones de la investigación (1,7), por lo cual estudios como este son el primer paso imprescindible antes de efectuar pesquisas con objetivos más precisos.…”
Section: Discussionunclassified
“…En otros estudios en el mismo modelo animal llevados a cabo por nuestro equipo de investigación, se ha corroborado esta conclusión, pues en el grupo inoculado por vía subcutánea se encontraron alteraciones en los parámetros oxidativos y metabólicos (principalmente en el perfil renal) (27). Sin embargo, en la literatura científica se ha registrado la presencia de diabetes moderada con la inoculación intraperitoneal de estreptozotocina en animales durante el periodo neonatal, aunque con variaciones en las dosis, los momentos y las cepas utilizadas (9,13,28,29), lo cual corrobora que el modelo debe seleccionarse en función del propósito y las condiciones de la investigación (1,7), por lo cual estudios como este son el primer paso imprescindible antes de efectuar pesquisas con objetivos más precisos.…”
Section: Discussionunclassified
“…24 In contrast, it already demonstrated no changes in oxidative stress profile from mild hyperglycemia. 25 It have been suggested that there may be temporal changes in enzyme activity that are both transitory and biphasic in nature. For instance, after prolonged hyperglycemia in severe diabetes (glycemia superior to 300 mg/dL), the induction of certain antioxidant enzymes or a return to normal values from previously decreased values may occur as a compensatory mechanism to respond to the constant exposure to increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…To reproduce the hyperglycemia of human uncontrolled type-1 diabetes, experimental models have been developed (Portha et al 1974;Tsuji et al 1988;Oh et al 1991;Caluwaerts et al 2003;Soulimane-Mokhtari et al 2005;Sinzato et al 2009). In our study, as expected, SD rats had the highest, and MD rats had intermediate circulating blood glucose levels throughout pregnancy compared to non-diabetic rats.…”
Section: Discussionmentioning
confidence: 99%